Thresholds: Gateways to the Nuclear Imagination - Dunlop, Gair (Journal of Contemporary Archaeology, 2015)
This photo essay summarises some investigations into the imagery and architectures of British nuclear research, in particular the fast reactor programme. I am interested in the interaction of the ‘nuclear imaginary’ and the actual sites in which the experimentation took place. My background is as a visual artist and researcher, with a particular interest in ‘entropic modernism.’ I define this as the exploration of modernism as lived experience, where the fading of 20th century ideals takes physical form. I consider the ‘nuclear imaginary’ as a constellation of anxieties, optimisms, technocratic and patriotic emotions and motivations, which leaves traces in factual material, the cinema and fiction of the time, and in propaganda and public discourse. The ‘imaginary future’ is a product not only of the tangible physicalities, the new infrastructures, the demographics of a rural population doubling and mutating into a scientific powerhouse; it’s inside our minds. It is important to consider the imagination as a part of the recruitment process to a specific kind of modern citizenship. When the actual future has rolled on by, and slower rhythms of a country town re-assert themselves, the idea of the future lingers on. The vestiges become rusty. Atomic fission has ceased. “The Atomics” remain.